Construction and Anti-Cancer Activity of a Self-Assembly Composite Nano-Delivery System Loaded with Curcumin - Liang Chen; Qiao Wu; Chen Yang; Xiulan Xin; Zhaochu Xu; Shuai Luo; Hao Liang (Molecules)
Natural products possess potent pharmacological activities and health benefits. However, drawbacks such as water insolubility, poor stability, and low bioavailability limit their practical applications. This research is dedicated to the development of suitable natural self-assembled nano-delivery systems to encapsulate natural molecule drugs, improving their dispersion and stability in aqueous solution. As a model drug, curcumin (Cur) was encapsulated in zinc–adenine nanoparticles (Zn–Adenine), based on the self-assembly of a coordination matrix material. Hyaluronic acid (HA) was further functionalized on the surface of Cur@(Zn–Adenine) to realize a tumor-targeted delivery system. The morphology was characterized through TEM and zeta potential analyses, while the encapsulation mechanism of the nanoparticles was researched via XRD and FTIR. The formed Cur@(Zn–Adenine)@HA nanoparticles exhibited good drug loading efficiency and drug loading rate. Moreover, compared to free Cur, Cur-loaded (Zn–Adenine)@HA showed enhanced pH stability and thermal stability. In particular, Cur@(Zn–Adenine)@HA demonstrated excellent biocompatibility and strong specificity for targeting CD44 protein on cancer cells. The above results indicate that (Zn–Adenine)@HA NPs can serve as an effective nano-delivery system for hydrophobic substances.